Thought Leadership In Organisations - Nurqhadiya, Abdul Kadir (Universiti Malaysia Sarawak (UNIMAS), 2020)
The objective of this paper is to review the existing literature on thought leadership in organisations and to determine the primary subjects researched, the subtopic or themes, methodology used, and the geographical area undertaken, to bridge the gap in comprehending and defines plus characterizes thought leaderships in organizations, to addresses a major void in the literature, and to date there are lack of studies that narrow down the focus to thought leadership specifically in organisational context. Other than, this study was held to answer these questions such as what are the issues connected with organizational thought leadership? What topics related to thought relationship that gain popularity throughout the 10 years and what not? And what can be proposed to future researcher in the context of thought leadership in organizations? This study uses Scopus and Google Scholar to comprehensively review 360 papers released between 2011-2020 with an objective of identifying key themes in the literature. The issues connected with organizational thought leadership would be on thought leadership competencies, thought leadership comprehension and thought leadership practices. On the other hand, topics related to thought leadership in organizations that gain popularity throughout the 10 years are understanding thought leadership at 66% and also identifying thought leadership at 83% within the 12 reviewed papers from 2009-2020. One research title suggestion for future researcher in this field is “Exploring Thought Leaders Competencies in Organization” in the context of Malaysia